(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the methodology of implementing a competency-based approach in mathematics lessons within higher pedagogical education. The study is grounded in the idea that modern mathematics instruction should move beyond the transmission of theoretical knowledge and focus on the formation of practical, cognitive, communicative, and analytical competencies. Particular attention is given to the pedagogical conditions that ensure effective competency development, including learner-centered instruction, problem-based tasks, interactive methods, differentiated assignments, and formative assessment strategies. The article analyzes how competency-oriented mathematics teaching contributes to the development of independent thinking, logical reasoning, mathematical literacy, and the ability to apply knowledge in real educational and life situations. It is argued that the competency-based approach strengthens students’ motivation, supports active participation in the learning process, and improves the quality of professional preparation of future teachers. The article also outlines the role of methodological planning, educational technologies, and teacher guidance in organizing mathematics lessons that meet contemporary educational requirements. The findings suggest that the systematic integration of competency-based instruction into mathematics teaching creates favorable conditions for developing intellectually active, methodologically prepared, and professionally competent future specialists